MODELLING OF SURFACE ROUGHNESS AND MATERIAL REMOVAL RATE IN LASER BEAM MACHINING OF AL2O3/CNT USING TAGUCHI TECHNIQUE - Yemmani Suresh Babu; Syed Altaf Hussain; B.Durga Prasad (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Laser machining stands as a leading noncontact method in advanced manufacturing. Its prowess lies in crafting intricate surfaces, structures, and electro-mechanical devices, often on a minute scale, using laser energy. Unlike traditional methods, this process relies on the thermophysical characteristics of materials rather than their mechanical traits. Crafting an optimal surface quality and material removal depends heavily on fine-tuning process parameters.In a recent study, laser beam machining using a nanosecond pulse ytterbium fiber laser on alumina ceramic was investigated. The focus was on understanding the impact of cutting speed, oxygen pressure, and the percentage of carbon nano tubes (CNT) in the alumina matrix on material removal efficiency and surface finish quality. This exploration delved into the development of Al2O3/CNT composites, analyzing variations in the weight percentages of carbon nano tube materials within the alumina structure.